Die SED in der Ära Honecker. Machtstrukturen, Entscheidungsmechanismen und Konfliktfelder in der Staatspartei 1971 bis 1989 - Malycha, Andreas (Quellen und Darstellungen zur Zeitgeschichte, 2014)
Andreas Malycha analyzes intra-party conflicts and decision-making processes in the inner power circle of East Germany`s SED (Socialist Unity Party). The study focuses on previously undocumented disputes about economic and social policy in the Honecker era, shedding new light on the stability and instability of the East German state.